Evaluation of the Fracture Resistance Offered by Three Different Intraorifice Barriers on Obturated Teeth: An In-vitro Study - Sonam Mangaonkar; Federico Foschi; Kristlee Sabrin Fernandes; Paul Chalakkal; Nilesh Kadam; Rajan Lambor (Journal of Clinical and Diagnostic Research, 2023)
Introduction: The mere placement of a restoration after obturation carries the risk of the presence of voids between them. These voids reduce overall strength and allow for leakage. The placement of Intraorifice Barriers (IOB) between the restoration and the obturated material has been known to have several advantages, including the prevention of microleakage, enhancement of strength, and improvement in Fracture Resistance (FR). Aim: To evaluate if, Smart Dentin Replacement (SDR) flow plus, Resin Modified Glass Ionomer Cement (RMGIC), and Biodentine increase the FR of Endodontically Treated Teeth (ETT) as IOB. Additionally, the study aimed to compare the FR between roots sealed using Endosequence and AH Plus sealers. Materials and Methods: This in-vitro study was carried out in the Department of Conservative Dentistry and Endodontics, Goa Dental College and Hospital, Bambolim, Goa, India over a period of four weeks, from October 2020 to November 2020. The study sample consisted of 160 mandibular premolar roots instrumented using ProTaper gold rotary files. These roots were obturated with Gutta Percha (GP) and divided into two groups based on the sealer used (Group I=Endosequence; Group II=AH Plus). Each group was further divided into four subgroups, including a control group, with each subgroup receiving an IOB. FR was tested using a universal testing machine, and the forces were statistically analysed using Two-way Analysis of Variance (ANOVA), One-way ANOVA, and posthoc Bonferroni tests. Results: SDR offered the greatest FR values of 583.08 N and 612.13 N in groups I and II, respectively. Roots sealed with AH Plus showed greater FR than those sealed with Endosequence. In both groups, the differences between IOB and the control group in terms of FR were found to be highly significant (p<0.001). Conclusion: SDR showed the greatest FR when compared with RMGIC and BD as IOB in ETT. Teeth restored with SDR and sealed with AH Plus offered the greatest FR.